2011
DOI: 10.1111/j.1445-5994.2011.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the use of immunomodulatory therapies in the Global Initiative for Asthma (GINA) step V asthma other than oral glucocorticosteroids

Abstract: Asthma is a major problem worldwide, which is estimated to affect 300 million individuals. The global prevalence ranges from 1% to 18% of the population. The incidence, morbidity and mortality of the condition have increased over the last 50 years despite the development of new anti-asthmatic drugs. Fewer than 1% of the asthmatic population are steroid-dependent, but these patients consume most of the resources and time at asthma units. The consensus documents published by professional societies all support a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Until omalizumab was first marketed in 2006, the international guidelines considered oral corticosteroids (OCs) to be the final step in the treatment of severe asthma patients ( Domingo et al., 2007 ). The use of certain immunosuppressive drugs was also proposed ( Domingo et al., 2009 ; Domingo et al., 2011a ) although they were not included in the guidelines. With the advent of biological treatments linked to the concept of precision medicine ( Jameson and Longo, 2015 ), it became necessary to phenotype patients ( Wenzel, 2012 ), and more recently to endotype them ( Lötvall et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Until omalizumab was first marketed in 2006, the international guidelines considered oral corticosteroids (OCs) to be the final step in the treatment of severe asthma patients ( Domingo et al., 2007 ). The use of certain immunosuppressive drugs was also proposed ( Domingo et al., 2009 ; Domingo et al., 2011a ) although they were not included in the guidelines. With the advent of biological treatments linked to the concept of precision medicine ( Jameson and Longo, 2015 ), it became necessary to phenotype patients ( Wenzel, 2012 ), and more recently to endotype them ( Lötvall et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 This reduction in OCS use is of importance because treatment with OCSs has a considerable impact on patients' lives owing to the associated corticosteroid-related adverse effects. [9][10][11] While all 3 studies reported the prevalence of adverse events (AEs) and assessed basic safety variables, the long-term safety and durability of the response to subcutaneous mepolizumab in patients with severe eosinophilic asthma are not fully established.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic asthma, inhaled/intravenous corticosteroids and magnesium sulphate are used in addition to long‐acting beta agonists, leukotriene receptor antagonists, anticholinergic medications (Shepherd et al , ), or mast cell stabilizer. However, patients who require frequent or continuous treatment of these medications receive little or no benefit because of the severe side effects when administered over long periods or at high doses (Domingo et al , ). Therefore, safer preventive and therapeutic agents for asthma need to be developed.…”
Section: Introductionmentioning
confidence: 99%